Changes in Cognitive Impairment in the Czech Republic - Seblova, Dominika; Brayne, Carol; Machů, Vendula; Kuklová, Marie; Kopecek, Miloslav; Cermakova, Pavla (Journal of Alzheimer's disease, 2019)
BACKGROUND: Studies from North America and Western Europe suggest stable or declining trends in impaired cognition across birth cohorts. OBJECTIVE: We aimed to examine changes in the age-specific prevalence of cognitive impairment in the Czech Republic. METHODS: The study used two samples from the population-based Czech Survey on Health, Ageing and Retirement in Europe. Age-specific prevalence of cognitive impairment (defined based on scores in verbal fluency, immediate recall, delayed recall, and temporal orientation) was compared between participants in wave 2 (2006/2007; n = 1,107) and wave 6 (2015; n = 3,104). Logistic regression was used to estimate the association between the wave and cognitive impairment, step-wise adjusting for sociodemographic and clinical characteristics. Multiple sensitivity analyses, focusing on alternative operationalizations of relative cognitive impairment, impact of missing cognitive data, and survival bias, were carried out. RESULTS: The most conservative estimate suggested that the age-specific prevalence of cognitive impairment declined by one fifth, from 11% in 2006/2007 to 9% in 2015. Decline was observed in all sensitivity analyses. The change was associated with differences in physical inactivity, management of high blood cholesterol, and increases in length education. CONCLUSION: Older adults in the Czech Republic, a country situated in the Central and Eastern European region, have achieved positive developments in cognitive aging. Longer education, better management of cardiovascular factors, and reduced physical inactivity seem to be of key importance.
Keywords: Male; epidemiology; stárnutí; senioři nad 80 let; Aged, 80 and over; cognitive impairment; Prospective Studies; Humans; Health Surveys; senioři; prospektivní studie; Česká republika; mužské pohlaví; Cognitive Dysfunction; Female; Czech Republic; prevalence; samostatný způsob života; Alzheimer’s disease; Aging; Aged; ženské pohlaví; trends; kognitivní dysfunkce; Longitudinal Studies; Independent Living; longitudinální studie; lidé; zdravotnické přehledy